PROGNOSTIC SIGNIFICANCE OF nm23 PROTEIN IN THE TUMORS OF PATIENTS WITH COLORECTAL CANCER - D. A. Golovkov; I. P. Moshurov; V. V. Delektorskaya; D. V. Sukhoverkov; M. B. Bykovtsev; R. I. Moshurov; L. O. Petrov (Исследования и практика в медицине)
Purpose. Study of expression of protein nm23 inprimary and secondary foci of colorectal cancer (CRC) taking in consideration the clinical and morphological features of the disease and the possibility of predicting the risk of distant metastases. Material and methods. The study included postoperative material of 264 CRC patients with I–IV stages of cancer. Immunohistochemical staining performed by biotin-streptavidin immunoperoxidase method on the paraffin tissue sections of primary colon tumors and their metastases in lymph nodes and liver using antibodies against nm23 protein (H‑1 and H‑2) (“Dako”, Denmark). The results were evaluated by semiquantitative method based on the staining intensity and the number of antigen-positive cells and localization of immunoreactivity in cancer cells.Results. During the immunohistochemical study of primary tumors of the colon the increase of the accumulation of nm23 protein was observed in 53.4% (141/264) studied cases. In nmtastasis of CRC the main patterns of expression of a marker characteristic of the corresponding primary tumors was preserved. Survival curves, computed according to the method of Kaplan-Meyer showed that patients with nm23‑positive staining of tumors show a lower 5‑year overall survival than patients with negative immunoreactivity in the tumor. Indicators of disease-free survival in patients with CRC also deteriorated in nm23‑negative status of tumors compared to nm23‑positive status.Conclusion. The overexpression of nm 23 protein were freqently detected in metastasizing primary tumors of colon and their liver metastases and was associated with a high risk of developing distant metastases, and poor outcome of the disease and the deterioration of the postoperative overall and disease-free survival of CRC patients. A high expression level of this marker is a sign of unfavorable prognosis for CRC patients.